2020
DOI: 10.1002/ppul.24898
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fractional exhaled nitric oxide for asthma management in children: A systematic review and meta‐analysis

Abstract: BackgroundFractional exhaled nitric oxide (FENO) is a noninvasive strategy for diagnosing and managing asthma, but limited evidence is available for the effects of FENO‐guided asthma management in children. This meta‐analysis aimed to evaluate the effectiveness of FENO for asthma management in children.MethodsIn total, six databases were searched, and 23 randomized controlled trials that compared the effects of FENO‐guided asthma management with those not using FENO in pediatric asthma were included. Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…23 Some added value has been shown in predicting response to inhaled corticosteroids and preventing exacerbations, but there was no effect on symptoms or use of medications. 24 Availability, cost, and variability due to unrelated exposures are probably reflected in the current infrequent use of FeNO monitoring, with moderate interest for intensification. 25 Airway hyperresponsiveness monitoring has been suggested as a strategy to improve outcomes in adult asthma, 26 but this has not been confirmed in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Some added value has been shown in predicting response to inhaled corticosteroids and preventing exacerbations, but there was no effect on symptoms or use of medications. 24 Availability, cost, and variability due to unrelated exposures are probably reflected in the current infrequent use of FeNO monitoring, with moderate interest for intensification. 25 Airway hyperresponsiveness monitoring has been suggested as a strategy to improve outcomes in adult asthma, 26 but this has not been confirmed in children.…”
Section: Discussionmentioning
confidence: 99%
“…Most physicians follow a typical monitoring schedule (Figure 1; eFigure 6 in Supplement 1), which includes regular visits every 2 to 6 months (median [IQR], 5.0 [2.5-8.0] months) for mild to moderate asthma and 1 to 3 months (median [IQR], 2.5 [1.0-2.5] months) for severe asthma, with each visit lasting 10 to 40 minutes (median [IQR], 25 [15][16][17][18][19][20][21][22][23][24][25] minutes for mild-moderate asthma and 25 [25][26][27][28][29][30][31][32][33][34][35] minutes for severe asthma) (Figure 1C and 1D). These parameters were very close to the perceived optimal (mild to moderate asthma: median [IQR] frequency, 5.0 [2.5-5.0] months; median [IQR] duration, 25 [15][16][17][18][19][20][21][22][23][24][25]…”
Section: Frequency Duration and Prioritiesmentioning
confidence: 99%
“…In patients with mild-to-moderate asthma, a recent meta-analysis demonstrated that a gradual ICS reduction when FeNO is below 50 ppb does not increase exacerbations [ 45 ]. The effectiveness of FeNO for asthma management was also confirmed when specifically evaluating paediatric populations [ 46 ]. Moreover, FeNO has been considered for asthma diagnostics, with values greater than 40 ppb showing the best performance (OR: 9.8) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, meta-regression analyses were also planned to evaluate the influence of a number of clinical and demographic variables on the observed results. For example, the length of follow-up after ICS initiation and the mean duration of chronic cough were quite heterogeneous in different studies and this may have significantly affected our findings [ 46 ]. The observation that such demographic and clinical covariates – even those related to cough aetiology ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente distintos estudios han demostrado que el manejo de pacientes asmáticos guiados por medición de FENO tienen menor número exacerbaciones, menos uso de corticoides orales, mejoría del VEF1, mayor tiempo transcurrido hasta la primera crisis de asma y menor riesgo de pérdida del control del asma (53)(54). Rol de la fracción espirada de óxido nítrico en el niño con diagnóstico de asma bronquial…”
Section: Rol Del Feno Para Guíar Tratamiento De Mantención En El Asma Bronquial Alérgica Th2unclassified